Using Animation Videos In Primary Education: Perspectives From Elementary Students - Marliyansah, Leni; Arini, Restu (Peneliti.net, 2025)
This study explores the use of animated videos in primary education from the perspective of elementary students. A qualitative approach was employed, combining classroom observations and semi-structured interviews with ten participants to gather in-depth insights into students' experiences. The findings reveal that six out of ten students found learning through animated videos more engaging and effective in improving vocabulary. Students reported a better understanding of new words and enhanced comprehension and demonstrated higher enthusiasm for the learning process. The study highlights how visual storytelling, motion graphics, and contextual animations contribute to a more immersive and memorable learning experience. These results highlight that animated videos serve as a valuable instructional tool fostering both vocabulary development and student engagement. Therefore, incorporating animated videos into English language instruction can significantly enhance vocabulary acquisition, and enrich overall learning experiences.